COMPARISON OF OPTICAL BIOMETRY AND A SCAN FOR CALCULATION OF INTRAOCULAR LENS POWER IN AGE RELATED NUCLEAR CATARACT AT TERTIARY CARE EYE HOSPITAL: Intraocular Lens Power - Rafique, Aisha; Zafar, Omar; Khan, Summaya (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare optical biometry and A-scan for calculating intraocular lens power in patients with nuclear cataract at tertiary care eye hospital.Study Design: Cross sectional comparative study. Place and Duration of Study: Armed Forces Institute of Ophthalmology, Pak Emirates Military Hospital, Rawalpindi, from Jul to Dec 2018.Methodology: In this study 70 eyes of 70 patients planned for cataract surgery by phacoemulsification underwent both optical biometry with intraocular lens master and ultrasound biometry applanation by A scan after informed consent. Intraocular lens power calculated by these two methods of biometry was compared. Phacoemulsification surgery was performed through a 2.3 mm superior temporal clear corneal incision. All patients underwent in the bag implantation of the same intraocular lens type. Results: The mean age of the patients was 62.89 ± 6.69 years. A significant (p-value